LITERATUR REVIEW: TINJAUAN TENTANG EFEKTIFITAS TERAPI NON FARMAKOLOGI TERHADAP PENURUNAN INTENSITAS NYERI PERSALINAN KALA I - Hasnah, Hasnah; Kb, Muhammad Allfian Rajab; Muaningsih, Muaningsih (Journal of Islamic Nursing, 2018)
Labor pain is a physiological condition. Pain originates from uterine contractions and cervical dilatation. With increasing volume and frequency of uterine contractions, the pain that is felt will be stronger, the peak of pain occurs in the active phase, where the complete opening is up to 10 cm and lasts around 4.6 hours for primiparas and 2.4 hours for multiparas. Handling pain in childbirth is the main thing that must be considered by health care providers when giving birth assistance. Therefore it is important to treat pain for the mother during labor. This review literature aims to find out non-pharmacological therapies that are effective in reducing pain at first stage of labor, so that it can be used as an alternative method of handling pain in labor. Method: This review literature is done by searching articles using electronic databases, namely google schoolar. Keywords used "Therapy", "Non Pharmacology", "Pain" and "Labor". The search results of the articles were found to be in accordance with the keywords and based on 2014-2018 as many as 430 articles, then the articles were reviewed, up to 4 articles studied and left to be reviewed. In an effort to reduce labor pain there are various methods that can be used, including massage therapy, aromatherapy, breath exercise, and murottal Al-Quran therapy. In this study the Murottal Al-Quran therapy became a focused therapy by researchers, with the reason that it was considered effective in reducing pain in the first stage of labor, it could also increase the value of the patient's faith in the Almighty. It can be concluded that many pain reduction methods can be used in reducing labor pain. Further studies related to nonpharmacological actions can be carried out more deeply and two or more therapies to reduce labor pain. Keywords: Therapy, Non Pharmacology, Pain, Labor